Tinjauan Sistematis Dampak Teknologi Kota Pintar terhadap Kualitas Hidup dan Lingkungan - Adiastoro, Mahendra; Ati Zuhrotal Afifah, Ning Imas; Arundaya, Adil; Pribadi, Feddy Setio; Aprilianto, Rizky Ajie (ELECTRON Jurnal Ilmiah Teknik Elektro, 2024)
This study conducted a Systematic Literature Review (SLR) to review the impact of smart city technologies on quality of life and environmental sustainability. Using the PRISMA method, this review systematically identified, screened, and selected relevant studies from reputable databases, focusing on recent publications from 2019 to 2024. The research addresses various aspects of smart city initiatives, including benefits, challenges, real-world applications, potential risks, and strategies to overcome implementation barriers. The results show that smart city technologies contribute positively to urban resource management, energy efficiency, and waste reduction, thereby improving quality of life and promoting sustainable urban development. However, data privacy, cybersecurity, and high implementation costs remain significant obstacles. Community engagement and customized approaches are identified as critical factors in the successful adoption of smart city initiatives. This study provides insights into strategies to optimize the benefits of smart city projects, offering a basis for further research and practical guidance for stakeholders in urban planning.